An Appraisal of the Environmental Protection Provisions in Petroleum Industry Act, 2021 - Akinsola, Ayodele Oladiran; Olayinka, Olaniyi Felix; Majekodunmi, Toyin Afolabi (NIU Journal of Legal Studies, 2025)
The development of petroleum resources has contributed immensely to the global energy demand and economic development over the past decades; however, it has left profound negative impacts on the natural environment and adverse human health effects in most oil-producing communities around the world. Apart from the loss of petroleum-derived revenue to corruption and ineffective government’s petroleum development policies, the Niger Delta region of Nigeria has experienced a wide range of environmental pollution, degradation, human health risks and socio-economic problems associated with petroleum exploration, development and production. The federal Government of Nigeria has responded by enacting laws and making Regulations. It has established various agencies to ensure the reduction of environmental hazards caused by petroleum extraction. Despite these efforts environmental degradation has continued unabated. This paper discusses the laws and Regulations before the Petroleum Industry Act (hereinafter referred to as Act) and the Act itself. It analyses the impact of the Act and its shortcomings. From the shortcomings or inadequacies identified, useful recommendations are made to align Nigerian Petroleum Industry practices with international standards. The paper adopts doctrinal methods of research. Keywords: Environment, Environmental law, environmental protection, Niger Delta